Biofunctional porous silicon micropatterns engineered through visible light activated epoxy capping and selective plasma etching. (April 2018) - Rodriguez, C.; Ahumada, O.; Cebrián, V.; Torres Costa, V.; Manso Silván, M.
Abstract: Porous silicon (PSi) is a versatile matrix with tailorable surface reactivity, which allows processing a diversity of biofunctional structures. An assembly process has been activated by catalyzing PSi oxidation with visible light, enabling subsequent binding with (3-glycidyloxypropyl)-trimethoxy-silane (GPTMS) in the submonolayer regime. A multispectroscopic approach has been followed to fully characterize the surface capped PSi. XPS has been used to trace the process of light induced oxidation and GPTMS assembly on supported PSi. Field emission SEM confirms that the surface topography is not modified by the activated assembly. To complement the chemical analysis of the bound GPTMS, FTIR and solid state NMR were used on functionalized PSi particles. Finally, the surfaces of GPTMS capped PSi have been successfully micropatterned by a masked Ar plasma etching process. The process gives rise to surface hydrophilic/hydrophobic contrasts, which are efficient in the selective binding of activated gold nanoparticles. The contrasts were applied to the local recognition of mouse serum proteins adsorbed on GPTMS functionalized PSi through an immunofluorescence assay. The results confirm the effectiveness of GPTMS capped PSi as adsorptive layer for immunosensing. Highlights: Surface functionalization of PSi structures with GPTMS activated by visible light. Multi-spectroscopic approach confirms oxidation of PSi and GPTMS binding. Solid state NMR suggests submonolayer low condensation degree of GPTMS. Plasma etching allows creating high surface energy contrasts of GPTMS/PSi. Surface contrast are functional for localized immunoassays.